Implementasi Manajemen Pembelajaran Bahasa Arab di Jurusan Hubungan Internasional Universitas Sriwijaya Indralaya - Gafur, Abdul; Nurhasan; Switri , Endang (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2020)
This paper explains how the implementation of Arabic language learning management in the Department of International Relations, Sriwijaya University, with the method used in this study is a qualitative research method. The purpose of this research is to find out how the implementation of Arabic language learning in the Department of International Relations, Sriwijaya University, which starts with Planning, Organizing, Actuanting and Controlling / Evaluating Arabic learning activities in the Department of International Relations, Sriwijaya University, and to find out the obstacles in its implementation.The results showed that this activity was sufficient in applying the management principles of Arabic language learning, even though it was still lacking. This can be seen from the process of planning, organizing and mobilizing it, although this still needs a lot of improvement